Advocating electrically conductive scaffolds with low immunogenicity for biomedical applications: a review - Ahmad Ruzaidi, Dania Adila; Mahat, Mohd Muzamir; Shafiee, Saiful 'Arifin; Mohamed Sofian, Zarif; Mohmad Sabere, Awis Sukarni; Ramli, Rosmamuhamadani; Osman, Hazwanee; Hamzah, Hairul Hisham; Zainal Ariffin, Zaidah; Sadasivuni, Kishor Kumar (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Scaffolds support and promote the formation of new functional tissues through cellular interactions with living cells. Various types of scaffolds have found their way into biomedical science, particularly in tissue engineering. Scaffolds with a superior tissue regenerative capacity must be biocompatible and biodegradable, and must possess excellent functionality and bioactivity. The different polymers that are used in fabricating scaffolds can influence these parameters. Polysaccharide-based polymers, such as collagen and chitosan, exhibit exceptional biocompatibility and biodegradability, while the degradability of synthetic polymers can be improved using chemical modifications. However, these modifications require multiple steps of chemical reactions to be carried out, which could potentially compromise the end product’s biosafety. At present, conducting polymers, such as poly(3,4-ethylenedioxythiophene) poly(4-styrenesulfonate) (PEDOT: PSS), polyaniline, and polypyrrole, are often incorporated into matrix scaffolds to produce electrically conductive scaffold composites. However, this will reduce the biodegradability rate of scaffolds and, therefore, agitate their biocompatibility. This article discusses the current trends in fabricating electrically conductive scaffolds, and provides some insight regarding how their immunogenicity performance can be interlinked with their physical and biodegradability properties.